Comments on the genus Zalarnaca Gorochov, 2005 (Orthoptera: Gryllacrididae: Gryllacridinae) with two new combinations and two new synonyms - Shi, Fuming; Du, Baojie; Bian, Xun (Zootaxa, 2017)
Two new combinations of the genus Zalarnaca Gorochov, 2005 are reported and illustrated, i.e. Zalarnaca (Glolarnaca) sinica (Li, Liu & Li, 2016) com. nov.; Zalarnaca (Glolarnaca) hainanica (Li, Liu & Li, 2016) com. nov. Also two synonyms are confirmed: Prosopogryllacris chinensis Li, Liu & Li, 2016 synonymized with Eugryllacris elongata Bian & Shi, 2016, and Prosopogryllacris incisa Li, Liu & Li, 2016 synonymized with Eugryllacris longifissa Bian & Shi, 2016. All material examined is deposited in the Museum of Hebei University.